Determinants of infant and young child feeding practices by mothers in two rural districts of Sindh, Pakistan: a cross-sectional survey - Gul Nawaz Khan; Shabina Ariff; Ubaidullah Khan; Atif Habib; Muhammad Umer; Zamir Suhag; Imtiaz Hussain; Zaid Bhatti; Asmat Ullah; Ali Turab; Ali Ahmad Khan; Alba Cecilia Garzon; et al. (BMC, 2017)
Abstract Background Infant and young child feeding (IYCF) practices during the first two years of life are important for the growth and development of a child. The aim of this study was to assess IYCF practices and its associated factors in two rural districts of Pakistan. Methods A cross-sectional study was conducted in two rural districts of Sindh province, Pakistan as part of a stunting prevention project between May and August 2014. A standard questionnaire on IYCF practices recommended by World Health Organization was used to collect information from 2013 mothers who had a child aged between 0 and 23 months. Results Only 49% of mothers initiated breastfeeding within one hour of birth. Thirty-seven percent of mothers exclusively breastfed their infants for six months. Seventy-percent mothers introduced complementary feeding at 6-8 months of age. Eighty-two percent of mothers continued breastfeeding for at least one year and 75% for at least two years of age. IYCF practices were not significantly different for boys and girls in the study area. Being an employed mother (AOR 2.14; 95% CI 1.02, 4.51) was positively associated with the early initiation of breastfeeding. Children who were born at a health facility (AOR 0.65; 95% CI 0.50, 0.84) and were aged six to eleven months (AOR 0.70; 95% CI 0.54, 0.90) were less likely to be have an early initiation of breastfeeding. Mothers aged 25 to 29 years (AOR 1.83; 95% CI 1.05, 3.18), being literate (AOR 1.79; 95% CI 1.15, 2.78), and higher income (AOR 10.6; 95% CI 4.40, 25.30) were more likely to have an improved dietary diversity. Being an employed mother (AOR 2.18; 95% CI 1.77, 4.03) and higher income were more likely to have minimum acceptable diet (AOR 9.7; 95% CI 4.33, 21.71). Conclusion IYCF practices were below the acceptable level and associated with maternal age, maternal illiteracy, unemployment, and poor household wealth status. Emphasis should be given to improve maternal literacy and reduction in poverty to improve IYCF practices.